2013
DOI: 10.2139/ssrn.2224580
|View full text |Cite
|
Sign up to set email alerts
|

Open Access, Social Norms & Publication Choice

Abstract: The aim of this paper is to shed light on scholarly communication and its current trajectories by examining academics' perception of Open Access, while also providing a reference case for studying social norm change. In this respect, the issue of publication choice and the role of Open Access journals casts light on the changes affecting the scientific community and its institutional arrangements for validating and circulating new research. The empirical investigation conducted also offers a useful vantage poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…This matches the results of other studies which have found that highly regarded authors and full professors can make different choices, such as not publishing in journals at all and instead leaving their writings in working paper versions (Ellison ), or more freely opting for OA journals (Migheli and Ramello ). Such authors in fact simply receive a lesser marginal benefit from their publication choice.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…This matches the results of other studies which have found that highly regarded authors and full professors can make different choices, such as not publishing in journals at all and instead leaving their writings in working paper versions (Ellison ), or more freely opting for OA journals (Migheli and Ramello ). Such authors in fact simply receive a lesser marginal benefit from their publication choice.…”
supporting
confidence: 89%
“…Therefore, despite the OA model's disruptive potential to better disseminate scientific advances and lower production, printing, and distribution costs (Houghton et al ), the scholarly communication system exhibits structural rigidities tied to the existing system of incentives, essentially stemming from social norms and prudential attitudes on the part of researchers (Migheli and Ramello ). The puzzle to unravel, therefore, concerns the signals produced by the existing RA system, which are not easily replicated in the OA realm without the help of some exogenous intervention or shock.…”
Section: Oa Publishing: Key Issuesmentioning
confidence: 99%
“…Science and health MOOCs tend to pick a license that is more open than those taught in business/law and humanities/social sciences. 6 This result is reminiscent of those of Migheli and Ramello [2013], Eger et al [2015] and Zhu [2017] in the research context. Science and health scholars also tend to be more proactive with respect to open access publishing practices, e.g.…”
Section: Empirical Analysismentioning
confidence: 83%
“…Today, scholarly publishing is without question an essential vehicle for actively participating in the scientific debate and for sustaining the invisible colleges of the modern research environment, which extend far beyond the borders of individual research institutions. However, it has also become a metric for measuring the productivity of researchers and the institutions in which they work (Carrasco & Ruiz-Castillo, 2013; Davis, 2009; Migheli & Ramello, 2013).…”
Section: Structural Features Of Modern Scholarly Publishingmentioning
confidence: 99%